PENGARUH LATIHAN MENENDANG PECING TERHADAP KECEPATAN TENDANGAN SABIT ATLIT PENCAK SILAT OKIDO PEKANBARU - Pernando Tri Chanko; Ramadi Ramadi; Aref Vai (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : The purpose of this study was to determine the speed of the crescent kick of OKIDO pencak silat athletes. When making observations, researchers see athletes while competing and training when doing a sickle kick, their kicks are easily captured by their opponents. Because in pencak silat the speed of menedang is very much needed, because if the foot has been caught the opponent can easily drop and get good points. The population in this study was OKIDO pencak silat athletes with a group of 15 people but the researchers took it based on age and sex, so the researchers used 4 athletes to be sampled. The technique used in this study is purposive sampling. Based on the t-test analysis produces tcount of 4.9 and t table of 2.132 means tcount> t table. It can be concluded that H1 is accepted. And based on the normality test by using the liliefors test from the pretest data kicking the kick, it produces Lo max 0.25 smaller than Ltable 0.381. Furthermore, given the kicking kick training for 16 meetings resulting in Lo max 0.1587 smaller than Ltabel 0.381, it can be concluded that the data are normally distributed.Key Words: Influence Of Exercise, Kick, Crescent Kick Pecing